Possibilities of Correcting Energy Metabolism Disorders and Adaptive Homeostasis in the Perioperative Period in Patients with Uterine Cancer - S. V. Tumanyan; T. I. Moiseenko; E. M. Franziyants; E. M. Nepomnyashya; V. A. Bandovkina (Антибиотики и Химиотерапия)
The aim of the study was to evaluate energy metabolism and adaptation potential, as well as the possibility of their differentiated correction in energy-deficient states in the postoperative period in patients with uterine body cancer.   Methods. The patients were divided into the main (N = 36) and control groups (N = 32) immediately before the surgery. In the main group, Remaxol® was introduced into the complex of treatment measures to correct energy metabolism before and during the perioperative period. An antihypoxant was not used in the control group. The state of energy metabolism and the type of energy deficiency were assessed by hemoglobin transport, oxygen consumption and extraction, glucose and lactate concentrations. The quantitative and qualitative composition of peripheral blood was studied in order to determine the nature of the adaptive response. The survey was conducted before surgery, on the 2nd and 5th days of the perioperative period.   Results. 69 % of patients had G1 differentiation of endometrial carcinoma. Excess weight > 26) was recorded in 68% of cases, regardless of the uterine body cancer (UBC) stage. Patients are comparable in age, as well as anthropometry. Analysis of the obtained results showed that the baseline background of UBC patients is characterized by various types of dysregulation of energy metabolism, disruption of the regulatory mechanisms of the physiological adaptation response, and the prevalence of the body's stress response. The use of Remaxol® contributed to the restoration of energy potential and adaptive homeostasis in the main group of patients in the perioperative period.   Conclusion. A differentiated approach to the dose selection of the anti-hypoxant used in this category of patients promotes leveling of emerging types of energy deficiency, restoration of adequate oxygen consumption and extraction, hemoglobin transport, remodulation of physiological adaptive homeostasis regulatory mechanisms, which will contribute to a favorable course of the perioperative period, as well as a decrease in the number of somatic and surgical complications in this category of patients.